2010
DOI: 10.1016/j.radphyschem.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of specific nanoparticles for targeting tumor angiogenesis using electron-beam irradiation

Abstract: International audienceAngiogenesis plays a critical role in both growth and metastasis of tumors. Vascular endothelial growth factor (VEGF) is an endogenous mediator of tumor angiogenesis. Blocking associations of the VEGF with its corresponding receptors (KDR) have become critical for anti-tumor therapy. Acyclo-peptide (CBO- P11), derived from VEGF, able to inhibit the interaction between the growth factor and its receptor, was synthesized in our laboratory to provide a target for angiogenesis. We have prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Radiation initiation is one of the cleanest grafting methods available, since molecular initiator or catalysts are not required. In a previous work, we reported the grafting of AA on PVDF nanoparticles after their irradiation (postradio-grafting) (19). However, electron paramagnetic resonance and differential scanning calorimetry studies showed a relative instability of radicals initiated under irradiation in comparison with PVDF films, decreasing the radical amount available for post-polymerization of AA.…”
Section: Synthesis and Characterization Of Pvdf Nanoparticlesmentioning
confidence: 96%
See 3 more Smart Citations
“…Radiation initiation is one of the cleanest grafting methods available, since molecular initiator or catalysts are not required. In a previous work, we reported the grafting of AA on PVDF nanoparticles after their irradiation (postradio-grafting) (19). However, electron paramagnetic resonance and differential scanning calorimetry studies showed a relative instability of radicals initiated under irradiation in comparison with PVDF films, decreasing the radical amount available for post-polymerization of AA.…”
Section: Synthesis and Characterization Of Pvdf Nanoparticlesmentioning
confidence: 96%
“…PVDF nanoparticles were prepared by emulsion polymerization of corresponding monomer (VF2) as previously described (19). Two different syntheses were run in the presence or in the absence of surfactant.…”
Section: Synthesis Of Pvdf Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Through a careful analysis of these iron oxide systems, the surface structure and ligand binding (chelation) configuration was determined, and in several cases were quite different from the standard single point attachment proposed by others. [58] 1 H HR-MAS NMR has also been used to look at the surface modification in polymer based NPs, including the monitoring of multiple synthetic steps employed during the peptidesurface modification of poly(vinylidene fluoride) (PVDF) nanoparticles, [60] or the surface modification of Dendron based NPs. [61] Polystyrene embedded silver clusters produced by a thermolysis reactions have also been characterized using HR-MAS NMR.…”
Section: Surface Modified Nanoparticlesmentioning
confidence: 99%